Colonial, refugee and allied civilians after the First World War immigration restriction and mass repatriation - Jenkinson, Jacqueline (Routledge studies in First World War history, 2020)
"Following the First World War and in actions which challenged Britain's reputation as a liberal democracy, various government departments implemented policies of mass repatriation from Britain of populations of colonial and friendly migrants and refugees. Many of those repatriated had played a significant part in the war effort and had given valuable service in the combat zones and on the home front: serving in the armed forces, in labour battalions and employed in key wartime industries; such as munitions work, the merchant navy and wartime construction. This book sets out to uncover why central government decided to implement a policy of repatriation of "friendly" peoples after the war. It also explores the imposition of wartime and post-war legal restrictions on these groups as part of a major shift in policy towards reducing the settlement and limiting the employment of overseas populations in Britain"--